Qualitative–quantitative multiscale pore characteristics of black shale from the Upper Ordovician and Lower Silurian black shale in the Southern Sichuan Basin, China - Han, Chao; Zhang, Yuetong; Wang, Guorui; Li, Hua; Zhang, Zhihui; Li, Qiang (Frontiers in Earth Science, 2022)
Accurate investigation of shale pores is critical to the assessment of shale-gas reservoir properties. Qualitative and quantitative methods have been commonly conducted in shale pore studies. In this study, we take the black shale from the Upper Ordovician and Lower Silurian black shale in the Southern Sichuan Basin as an example. Both qualitative and quantitative methods were used to study the pores at multiple scales, and we discuss the effectiveness of shale pore detection by multiple methods. The following results were obtained: 1) The black shale is composed of quartz, feldsaper, calcite, dolomite and clay minerals in the study area, and its average TOC and porosity are 2.19% and 2.12%, respectively. 2) The CT results show that the pore size of macropores (pore size >0.5 μm) mainly ranges from 2 μm to 16 μm. Nitrogen adsorption analysis shows that organic-rich shale has abundant organic matter pores with narrow necks and wide bodies. The pores of organic-poor shale are mainly composed of mineral-associated pores with narrow slit shapes. The NMR results show that with increasing TOC, the left peak T2 relaxation times move leftwards, meaning that organic matter pores have a larger pore size than matrix pores at the mesopore scale. 3) CT data identify lamellation fractures and bed-cutting fractures, and their development is controlled by mineral type and content, TOC and laminae density. 4) The determination of segmentation thresholds in CT and transverse surface relaxivity in NMR seriously affects the accuracy of the results.